TCP/IP versus VIA on Network of Workstations - Lobosco, Marcelo; Silva, Anderson Faustino da; Costa, Vítor Santos; Amorim, Claudio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2001.22202, 2001)
This paper evaluates the performance gains provided by VIA, ao user-level communication protocol, when compared to TCP/IP, a traditional, multilayered communication protocol. To achieve this purpose we run five distinct applications using the same network card and switch, and just change the communication protocol. For all but one application, the speedup of TCP/IP was between 28% and 97% that of achieved by VIA. We further run the same applications with a hardware implementation of VIA, to evaluate the gains that a hardware implementation could offer over a software implementation. For applications with high bandwidth demand, the hardware support helped to improve performance from 20% to 114%. Surprisingly, for one application, TCP/IP performs equally to the hardware implementation.